2016
DOI: 10.1016/j.chroma.2016.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial effects of the configuration of the cationic and the anionic chiral subunits of four zwitterionic chiral stationary phases leading to reversal of elution order of cyclic β-amino acid enantiomers as ampholytic model compounds

Abstract: In a systematic way enantioseparations of non-methylated and the corresponding N-monomethylated ampholytic cyclic ß-amino acids were carried out on four zwitterionic chiral stationary phases (CSPs; ZWIX(+)™, ZWIX(-)™, ZWIX(+A), ZWIX(-A)). CSPs were based on the combinations of quinine and quinidine as the cationic and of (R,R)- and (S,S)-aminocyclohexane sulfonic acid as the anionic sites. In polar-ionic mobile phase systems, the effects of the composition of the bulk solvents, the additives, the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 39 publications
8
17
0
Order By: Relevance
“…The data obtained on ZWIX columns revealed that, in general, an increasing counterion concentration resulted in reduced retention factors, as expected for ion‐exchangers. The slopes of the log k versus log c plots in this study (0.25–0.31) are in accordance with our results obtained on ZWIX phases working in zwitterionic mode . However, ZWIX phases working in a “uni‐ionic” mode as anion‐exchanger or cation‐exchanger exhibited steeper slopes (0.6–1.0).…”
Section: Resultssupporting
confidence: 91%
“…The data obtained on ZWIX columns revealed that, in general, an increasing counterion concentration resulted in reduced retention factors, as expected for ion‐exchangers. The slopes of the log k versus log c plots in this study (0.25–0.31) are in accordance with our results obtained on ZWIX phases working in zwitterionic mode . However, ZWIX phases working in a “uni‐ionic” mode as anion‐exchanger or cation‐exchanger exhibited steeper slopes (0.6–1.0).…”
Section: Resultssupporting
confidence: 91%
“…It is interesting to note that the slopes of the log k versus log c plots were changed in a very narrow range, between −0.20 and −0.30 for all the SAs studied, in accordance with slopes obtained for zwitterionic columns working in zwitterionic mode . The amino acids is expected to have zwitterionic character, and able to bind to the SO through the formation of double ion‐pairs.…”
Section: Resultssupporting
confidence: 77%
“…Under the studied conditions, practically identical slopes were obtained for each enantiomer on all four CSPs, thus the individual enantioselectivity characteristics remained almost constant when the counter-ion concentration changed. It is interesting to note that the slopes of the log k versus log c plots were changed in a very narrow range, between −0.20 and −0.30 for all the SAs studied, in accordance with slopes obtained for zwitterionic columns working in zwitterionic mode [22,35]. The amino acids is expected to have zwitterionic character, and able to bind to the SO through the formation of double ion-pairs.…”
Section: Influence Of Counter-ion Concentrationsupporting
confidence: 81%
“…The plot of ln α versus 1/T was linear ( r 2 > 0.97), meaning that the conformation of the chiral selectors remains essentially invariant at 15–40°C [35]. The calculated values of ΔΔH0 and ΔΔS0 were negative with ACN as the mobile phase, indicating that the separation process was controlled by enthalpy [36]. However, relatively small positive ΔΔS0 values were observed in the case of MeOH, accompanied by small absolute values of ΔΔH0, indicating that the separation of enantiomers in MeOH was achieved by both enthalpic and entropic contributions.…”
Section: Resultsmentioning
confidence: 99%